Defying c-Abl signaling circuits through small allosteric compounds - Gonfloni, Stefania (Frontiers in Genetics, 2014)
Many extracellular and intracellular signals promote the c-Abl tyrosine kinase activity. c-Abl in turn triggers a multitude of changes either in protein phosphorylation or in gene expression in the cell. Yet, c-Abl takes part in diverse signaling routes because of several domains linked to its catalytic core. Complex conformational changes turn on and off its kinase activity. These changes affect surface features of the c-Abl kinase and likely its capability to bind actin and/or DNA. Two specific inhibitors (ATP-competitive or allosteric compounds) regulate the c-Abl kinase through different mechanisms. NMR studies show that a c-Abl fragment (SH3-SH2-linker-SH1) adopts different conformational states upon binding to each inhibitor. This supports an unconventional use for allosteric compounds to unraveling physiological c-Abl signaling circuits.